2013
DOI: 10.5603/cj.2013.0023
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects in Kabuki syndrome

Abstract: their etiology, clinical presentations and long-term prognosis. (Cardiol J 2013; 20, 2: 121-124)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
(49 reference statements)
1
12
0
3
Order By: Relevance
“…With respect to congenital heart defects, the major types associated with Kabuki syndrome are left-sided obstructions and aortic dilation, coarctation of the aorta (COA), atrial septal defects (ASDs), ventral septal defects (VSDs), and tetralogy of Fallot (TOF), among others [ 32 , 33 ]. In our series, two patients presented with ASDs.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to congenital heart defects, the major types associated with Kabuki syndrome are left-sided obstructions and aortic dilation, coarctation of the aorta (COA), atrial septal defects (ASDs), ventral septal defects (VSDs), and tetralogy of Fallot (TOF), among others [ 32 , 33 ]. In our series, two patients presented with ASDs.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics of MLL2 mutation-positive cases did not differ significantly from MLL2 mutation-negative cases with the exception that renal anomalies were more common in MLL2 mutation-positive cases. MLL2 carriers obviously showed more frequently a typical facial gestalt compared with non-carriers [11].…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, visceral cartilages were significantly affected in kmt2d zy59 embryos ( (34). The spectrum of CHD is wide, with prevalence of aortic coarctation, hypoplastic left heart and other left-sided obstructive defects (14,15,34). Previous studies of a mouse cardiomyocyte conditional kmt2d deletion demonstrated that Kmt2d is required in cardiac precursors and cardiomyocytes (22).…”
Section: Kmt2d Zy59 Mutants Exhibit Anomalous Palate Development and mentioning
confidence: 99%
“…Kabuki Syndrome type I (KS, OMIM#147920) is a rare multi-systemic disorder, manifested by craniofacial anomalies including cleft lip/palate and microcephaly, hearing loss, neurodevelopmental defects, epilepsy, skeletal and skin abnormalities, and congenital heart defects (CHD) (1) (2-4) (5-7) (8) (9)(10)(11). While there is variable expressivity of the clinical hallmarks (8,12), CHD is present in ~70% of KS patients, with a unique predilection for left-sided obstructive lesions, including hypoplastic aortic arch, coarctation of the aorta and hypoplastic left heart syndrome (13)(14)(15)(16)(17). De-novo pathogenic variants in Histone-lysine N-methyltransferase 2D (KMT2D) are causative in up to 76% of KS patients (18,19).…”
Section: Introductionmentioning
confidence: 99%